Evaluation of the efficacy of mass prophylaxis with Arsenicum album 30c in mitigating the spread of COVID-19 in tribal communities of Nashik, India: a field study - Bagmar, Kamlesh; Prasad, G. B.; Nimbhore, Vishal; Dharne, Varsha; Yadav, Subhash (International Journal Of Community Medicine And Public Health, 2025)
Mass prophylaxis has long been vital in public health. This study examines the effectiveness, challenges, and ethical aspects of a COVID-19 mass prophylaxis campaign using homeopathy in tribal villages with limited healthcare access, conducted by the Motiwala Homoeopathic Medical College and Hospital. This study aimed to assess the effectiveness of a mass homeopathic prophylaxis program (Arsenicum Album 30) in preventing COVID-19 outbreaks in tribal communities and to identify implementation challenges in resource-limited rural areas. A mass administration of Arsenicum Album 30 was conducted between September 10-17, 2020, across five tribal villages in Nashik, India (population 9,586), following WHO and CCRH recommendations. Distribution involved medical staff and local health workers, with post-intervention disease surveillance. Before the campaign, one COVID-19 case existed in Mahadeopur. Post-intervention, three more cases emerged in the same village, all recovering at home with negative family tests. No new cases were reported in the other four villages until the end of December 2020. Conclusion: The mass administration of Arsenicum Album 30 in Nashik's tribal villages during high transmission appeared to limit virus spread. Research on implementation challenges in tribal populations is very crucial.